Physical, psychosocial, and organisational factors relative to sickness absence: a study based on Sweden Post. Issue 3 (1st March 2001) - Voss, M; Floderus, B; Diderichsen, F
Abstract : OBJECTIVE: To analyse incidence of sickness for women and men relative to potential aetiological factors at work—physical, psychosocial, and organisational. METHODS: The study group comprised 1557 female and 1913 male employees of Sweden Post. Sickness absence was measured by incidence of sickness (sick leave events and person-days at risk). Information on explanatory factors was obtained by a postal questionnaire, and incidence of sickness was based on administrative files of the company. RESULTS: Complaints about heavy lifting and monotonous movements were associated with increased risk of high incidence of sickness among both women and men. For heavy lifting, an odds ratio (OR) of 1.70 (95% confidence interval (95% CI) 1.22 to 2.39) among women, and OR 1.70 (1.20 to 2.41) among men was found. For monotonous movements the risk estimates were OR 1.42 (1.03 to 1.97) and OR 1.45 (1.08 to 1.95) for women and men, respectively. Working instead of taking sick leave when ill, was more prevalent in the group with a high incidence of sickness (OR 1.74 (1.30 to 2.33) for women, OR 1.60 (1.22 to 2.10) for men). Overtime work of more than 50 hours a year was linked with low incidence of sickness for women and men. Among women, 16% reported bullying at the workplace, which was linked with a doubled risk of high incidence of sickness (OR 1.91 (1.31 to 2.77)). For men, the strongest association was found for those reporting anxiety about reorganisation of the workplace (OR 1.93 (1.34 to 2.77)). CONCLUSIONS: Certain physical, psychosocial, and organisational factors were important determinants of incidence of sickness, independently of each other. Some of the associations were sex specific.